(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The rapid shift to online education has transformed the landscape of teaching and learning, presenting both opportunities and challenges. This article explores the efficiency of various online teaching strategies, including interactive learning, multimedia resources, asynchronous formats, frequent feedback, and community building. By analyzing how these strategies engage students, cater to diverse learning styles, and foster a supportive environment, the article highlights the importance of a thoughtful approach to online education. The findings suggest that effective online teaching not only enhances comprehension and retention but also prepares students for future challenges in a digital world. Continuous adaptation and innovation are crucial for maximizing the impact of online learning.